Lahan, Gender, dan Kuasa: Sebuah Studi tentang Ketidaksetaraan dalam Akses Kepemilikan Tanah di Kalangan Petani Perempuan di Tasikmalaya - Nisa Khoerunisa; Faisal Fadilla Noorikhsan; Nur Rahmi Ghayatri; Rendi Wandani (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2026)
in land ownership and control between men and women remains an agrarian issue that affects farmers’ well-being. Although studies on gender and agrarian issues have advanced, research on the relationship between agrarian governance, policy implementation, and women’s access to agrarian resources at the local level remains limited. This study aims to analyze land ownership disparities among female farmers in Tasikmalaya City and to examine how government agrarian policies are designed to improve their well-being. The study employed a descriptive qualitative approach through in-depth interviews and Focus Group Discussions (FGDs) with female farmers and relevant government agencies. The findings indicate that land ownership remains predominantly male-dominated; women are more likely to be farm laborers or family workers with lower wages, and they face limited access to land, capital, technology, and decision-making. The implementation of agrarian reform and the Sustainable Food Agricultural Land Protection (PLP2B) has not been fully gender-responsive due to institutional capacity constraints, a lack of gender-disaggregated data, and low female involvement in policy processes. Nevertheless, women remain actively engaged through Women Farmers’ Groups (KWT) and household food management. This study demonstrates that agrarian inequality is not only related to land distribution but also to governance and the implementation of public policies. Therefore, more inclusive and gender-responsive agrarian policies are needed to strengthen women farmers’ access, participation, and well-being.